The organs of local self-government in the providing system of rights and freedoms of man and citizen - Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article are describes the questions of participation of the organs of local self-government in the providing system of rights and freedoms of man and citizen. Also, an author adds the detailed analysis of participation question of other subject in the mechanism of providing of rights and freedoms of man and citizen and basic tendencies which exist in this sphere.